Differences in eating habits/behaviours and eating disorders symptoms in adolescents from a rural and a urban school - Santos, José (2013)
Introduction: Differences in eating habits/behaviours and eating disorders (ED) symptoms in adolescents from rural and urban schools has not been very considered, particularly in Portugal. Objectives: explore differences between students who attend rural and urban schools in eating habits/behaviors and ED symptoms; verify if there are differences regarding Body Mass Index (BMI) by school area. Methods: 282 adolescents students (mean age = 14,5; SD = 1,69; variation = 12-18 years old; urban subsample = 126, 44,7%), studying in two schools, one from an urban area and another from a rural area answered sociodemographic questions, eating habits/behaviours items and EAT-25 (Eating Attitudes Test-25). Results: Most of the adolescents from both schools have breakfast and drink milk daily. Moreover, they eat vegetables and fruits daily or weekly and only rarely fast-food. Adolescents that practice a sport eat more fruits/vegetables. Adolescents attending a rural school ingest more vegetables and less fast-food. ED symptoms (EAT-25) present a lower prevalence, comparing to a young adults sample. There were no significant differences in all the EAT-25 dimensions, EAT total score and BMI by school area. Conclusions: Eating habits/behaviours seem to be positive in both schools (e.g. most adolescents have breakfast daily). There were only some small differences between the two schools in particular eating habits but adolescents from the two areas do not seem to differ in ED symptoms and BMI, which is not in accordance with the literature that tends to signal urban areas as a “risk factor” for dysfunctional eating behaviors.